Cohort study on the differential expression of inflammatory and angiogenic factors in thrombi, cerebral and peripheral plasma following acute large vessel occlusion stroke. Issue 10 (October 2022) - Scott, Xavier O; Chen, Stephanie H; Hadad, Roey; Yavagal, Dileep; Peterson, Eric C; Starke, Robert M; Dietrich, W Dalton; Keane, Robert W; de Rivero Vaccari, Juan Pablo
Inflammation plays an important role in the pathogenesis of stroke. The differential expression of inflammatory and angiogenic factors in thrombi and plasma remain undefined. In this observational cohort study, we evaluated angiogenic factors and inflammatory cytokines, in cerebral thrombi, local cerebral plasma (CP), and peripheral plasma (PP) in patients with acute ischemic stroke. Protein analysis of thrombi, CP and PP were used to measure angiogenic and inflammatory proteins using electrochemiluminescence. Our data indicate that VEGF-A, VEGF-C, bFGF, IL-4, IL-13, IL-1β, IL-2, IL-8, IL-16, IL-6 and IL-12p70 were higher in the thrombi of acute ischemic stroke patients than in the CP and PP of stroke patients. Moreover, the protein levels of GM-CSF were lower in the PP than in the CP and the clot. Moreover, VEGF-D, Flt-1, PIGF, TIE-2, IL-5, TNF-β, IL-15, IL-12/IL-23p40, IFN-γ and IL-17A were higher in PP and CP than in thrombi. Our results show that cytokines mediating the inflammatory response and proteins involved in angiogenesis are differentially expressed in thrombi within the cerebral and peripheral circulations. These data highlight the importance of identifying new biomarkers in different compartments of the circulatory system and in thrombi that may be used for the diagnosis and treatment of stroke patients.